Peculiarities of cardio-respiratory relationships in qualified athletes with different types of heart rhythm regulation according to respiratory maneuver data - Oleksandr Romanchuk; Oleksandr Romanchuk (Frontiers in Sports and Active Living)
IntroductionOur goal was to determine the differences in changes in cardiovascular and cardiorespiratory interaction indicators during a respiratory maneuver with a change in breathing rate in athletes with different types of heart rate regulation.MethodsThe results of a study of 183 healthy men aged 21.2 ± 2.3 years, who were systematically involved in various sports, were analyzed. According to the results of the analysis of the HRV study during spontaneous breathing, the athletes were divided into 4 groups taking into account the type of heart rate regulation (HRR). Group 1 (with type I) consisted of 53 people, group 2 (with type II)—29 people, group 3 (with type III)—85 people, group 4 (with type IV)—16 people. The methodology for studying the cardiorespiratory system included combined measurements of the respiratory and cardiovascular system activity indicators in a sitting position using a spiroarteriocardiorhythmograph. The duration of the study was 6 min.ResultsAccording to changes in cardiorespiratory and cardiovascular interaction indicators during controlled breathing with a frequency of 6 and 15 per minute (CR6 and CR15), it is shown that with a pronounced predominance of parasympathetic influences (type IV) in conditions of excessive cardiorespiratory control and moderate hyperventilation, differences in changes in arterial baroreflex sensitivity (δBRLF and δBRHF) are noted in comparison with other HRR. Athletes with type IV at CR6 in δBRLF significantly differ from athletes with type III (p = 0.026) and do not differ from athletes with type II (p = 0.141). In δBRHF significantly (p = 0.038 and p = 0.043)—from athletes with types I and II. It is shown that with the predominance of sympathetic influences (types I and II), the reactivity of BRS (δBRLF and δBRHF) in response to moderate hyperventilation (CR15) is significantly lower. Changes in the Hildebrandt index and the volume synchronization index additionally differentiate HRR associated with a moderate and pronounced predominance of sympathetic and parasympathetic influences.ConclusionThe use of a respiratory maneuver in a combined study of the cardiorespiratory system in the conditions of current control of athletes showed informativeness in the differentiation of HRR types and states of functional overstrain.